2022
DOI: 10.1177/10556656221075935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dimension and Bridging of Sella Turcica and Presence of Ponticulus Posticus in Individuals With and Without Cleft: A Comparative Study

Abstract: Objective Sella turcica abnormalities such as sella turcica bridging (STB) have been observed frequently among patients with craniofacial anomalies. Ponticulus posticus (PP) is an important structure and its presence causes complications during surgeries. Due to the importance of these structures, this study aimed to evaluate the prevalence of STB, PP, and dimensions of the sella turcica in individuals with and without cleft. Design A cross-sectional study. Setting Orthodontic and Radiology Departments in a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The ponticulus posticus, often known as the "lit- et al, 2001). However, the majority of the studies in the literature assessed the prevalence on lateral cephalograms, where it was observed that the prevalence of PP was comparatively lower (Mosavat et al, 2023;Gibelli et al, 2016;Giri et al, 2017;Adisen et al, 2017;Di Venere et al, 2022), as compared to CBCT or CT studies (Bayrakdar et al, 2018;Tripodi et al, 2019;Buyuk et al, 2017;Martiniz et al, 2021;Sekerci et al, 2015) 3). This was consistent with the findings of…”
Section: Discussionmentioning
confidence: 99%
“…The ponticulus posticus, often known as the "lit- et al, 2001). However, the majority of the studies in the literature assessed the prevalence on lateral cephalograms, where it was observed that the prevalence of PP was comparatively lower (Mosavat et al, 2023;Gibelli et al, 2016;Giri et al, 2017;Adisen et al, 2017;Di Venere et al, 2022), as compared to CBCT or CT studies (Bayrakdar et al, 2018;Tripodi et al, 2019;Buyuk et al, 2017;Martiniz et al, 2021;Sekerci et al, 2015) 3). This was consistent with the findings of…”
Section: Discussionmentioning
confidence: 99%
“…The ponticulus posticus, often known as the "lit- et al, 2001). However, the majority of the studies in the literature assessed the prevalence on lateral cephalograms, where it was observed that the prevalence of PP was comparatively lower (Mosavat et al, 2023;Gibelli et al, 2016;Giri et al, 2017;Adisen et al, 2017;Di Venere et al, 2022), as compared to CBCT or CT studies (Bayrakdar et al, 2018;Tripodi et al, 2019;Buyuk et al, 2017;Martiniz et al, 2021;Sekerci et al, 2015). In fact, Kim 3).…”
Section: Discussionmentioning
confidence: 99%